IMPLANTAÇÃO DE RECICLAGEM DE LIXO EM UMA UNIDADE DE ALIMENTAÇÃO E NUTRIÇÃO (UAN) NO MUNICIPIO DE IJUI/RS - Ali, Nara C. A.; Neuberger, Suelen; Busnello, Maristela B. (Salão do Conhecimento, 2013)
Resumo